T2Bacteria and T2Resistance Assays in Critically Ill Patients with Sepsis or Septic Shock: A Descriptive Experience - Daniele Roberto Giacobbe; Francesca Crea; Paola Morici; Laura Magnasco; Vincenzo Di Pilato; Federica Briano; Edward Willison; Rachele Pincino; Silvia Dettori; Stefania Tutino; Simone Esposito; Erika Coppo; et al. (MDPI AG, 2022)
The use of rapid molecular tests may anticipate the identification of causative agents and resistance determinants in the blood of critically ill patients with sepsis. From April to December 2021, all intensive care unit patients with sepsis or septic shock who were tested with the T2Bacteria and T2Resistance assays were included in a retrospective, single center study. The primary descriptive endpoints were results of rapid molecular tests and concomitant blood cultures. Overall, 38 combinations of T2Bacteria and T2Resistance tests were performed. One or more causative agent(s) were identified by the T2Bacteria assay in 26% of episodes (10/38), whereas negative and invalid results were obtained in 66% (25/38) and 8% (3/38) of episodes, respectively. The same pathogen detected by the T2Bacteria test grew from blood cultures in 30% of cases (3/10). One or more determinant(s) of resistance were identified by the T2Resistance assay in 11% of episodes (4/38). Changes in therapy based on T2Bacteria and/or T2Resistance results occurred in 21% of episodes (8/38). In conclusion, T2Bacteria/T2Resistance results can influence early treatment decisions in critically ill patients with sepsis or septic shock in real-life practice. Large, controlled studies remain necessary to confirm a favorable impact on patients' outcomes and antimicrobial stewardship interventions.